PERENCANAAN PELEBARAN APRON BANDAR UDARA DENGAN METODE FEDERAL AVIATION ADMINISTRATION (FAA) (Studi Kasus Pelebaran Apron Bandar Udara Abdul Rachman Shaleh Malang) - Helmi Hermawan, Marjono, Trias Rahardianto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2014)
Current conditions of available capacities at Abdul Rachman Saleh Airport Malang can only accomodate four planes. The increasing number of aircraft departures and arrivals at The airport by 4.7 percent per year, requires accordance with the requirements. Due to the increasing numbers of departure and arrival, apron enlargement design for the next five year was made using FAA method. The objective of the study is to find out the area of the apron enlargement, pavement depth including the time and cost. CBR data were obtained from Polytechnic soil laboratory, arrival, departure and layout data were from Department of Transportation Malang. From data obtained FAA method is used to determine the enlargement and pavement depth . The calculations result in 11,253 m2 apron enlargement at a depth of 24 cm at IDR 4,897,100,000 in 133 work days.Keywords: enlargement apron, apron pavement, FAA